Analysis of Transaminase and Phosphatase Levels in Lead (Pb)-Exposed Fish, Clarias gariepinus: Implications of Environmental Contamination - Onadje, Festus Ovwighose; Akalusi, Kesiena Emmanuel (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2024)
Sub-adults of the African catfish Clariasgariepinus were exposed to sublethal concentrations (0.0mg/l, 0.4mg/l and 0.8mg/l) of lead in a static bioassay for 96 hours to analyse the activities of Glutamic Oxaloactic Transaminase (GOT), Glutamic Pyruvate Transaminase (GPT), Acid Phosphatase (ACP) and Alkaline Phosphatase (ALP) in the serum, liver and kidney of the fish. The various biochemical enzymes were tested according to the reagent kit manufacturer's instructions. Results from statistical ANOVA at the 0.05 probability level revealed no significant difference (P>0.05) between the activities of the parameters under test and the control. GPT and ACP showed substantial evidence of enzyme reversibility, whereas GOT activity showed a dose-dependent impact, and ALP showed fragile evidence. The toxicant (Lead) caused organ dysfunction, enzyme inhibition, metabolic impairment, and organ damage, and it can be inferred from the results in general that these biochemical parameters show marked alterations. The reaction patterns of these organs to stress follow the order serum>liver>kidney. As a result, these biochemical measures can be handy instruments for monitoring biochemical pollution.